2000
DOI: 10.1111/1467-6494.00126
|View full text |Cite
|
Sign up to set email alerts
|

A Motivational Perspective on Risky Behaviors: The Role of Personality and Affect Regulatory Processes

Abstract: The present study tested a motivational model in which personality influences on risky behaviors were hypothesized to be primarily indirectly mediated, by shaping the nature and quality of emotional experience as well as characteristic styles of coping with these emotions. This model was tested in a representative community sample of 1,666 young adults, aged 18 to 25 years old. Results revealed strong support for the model, indicating that broad traits related to neuroticism and extraversion promote involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
381
3
21

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(441 citation statements)
references
References 43 publications
29
381
3
21
Order By: Relevance
“…The co-occurrence of multiple types of risky behaviors is particularly worrisome as it increases the likelihood of negative long-term consequences (e.g., drug dependency, legal troubles, and unplanned pregnancy) as well as predicts poorer psychosocial functioning throughout adulthood (Bardone, Moffit, Caspi, & Dickson, 1996;Markey, Markey, & Tinsley, 2003). Thus, as the current study examined vulnerability/protective factors that are likely to predict a broad array of risky behaviors and utilized a sample that is likely to engage in an inconsistent range of risky behaviors, in line with past research, the current study examined broad-based engagement in risky behaviors (e.g., Cooper, Agocha, & Sheldon, 2000;Markey et al, 2003;Youngblade, Curry, Novak, Vogel, & Shenkman, 2006).…”
Section: Risky Behavior Engagementmentioning
confidence: 91%
“…The co-occurrence of multiple types of risky behaviors is particularly worrisome as it increases the likelihood of negative long-term consequences (e.g., drug dependency, legal troubles, and unplanned pregnancy) as well as predicts poorer psychosocial functioning throughout adulthood (Bardone, Moffit, Caspi, & Dickson, 1996;Markey, Markey, & Tinsley, 2003). Thus, as the current study examined vulnerability/protective factors that are likely to predict a broad array of risky behaviors and utilized a sample that is likely to engage in an inconsistent range of risky behaviors, in line with past research, the current study examined broad-based engagement in risky behaviors (e.g., Cooper, Agocha, & Sheldon, 2000;Markey et al, 2003;Youngblade, Curry, Novak, Vogel, & Shenkman, 2006).…”
Section: Risky Behavior Engagementmentioning
confidence: 91%
“…Although coping motives are shown to be associated with consequences in college students (Carey and Correia, 1997;Kassel et al, 2000), evidence that coping motives are associated with greater alcohol use is more equivocal. Although some research supports an association (Cooper et al, 2000;Labouvie and Bates, 2002), other research, particularly with college students, has not shown a direct link between coping motives and alcohol use (LaBrie et al, 2012;Magid et al, 2007;Merrill and Read, 2010;Patrick et al, 2011). Of importance, however, theory and data suggest that coping motives predict alcohol consequences regardless of quantity or frequency of drinking (Cooper et al, 1995;Molnar et al, 2010;Patrick et al, 2011;Read et al, 2003).…”
Section: Drinking Motives As Predictors Of Alcohol Use and Consequencesmentioning
confidence: 99%
“…Although norms may be especially relevant for socially focused drinkers because of the social comparison component of norms, they may be less relevant for coping-motivated drinkers. Drinking to cope with negative affect has been identified as an indicator of heavy (Cooper et al, 2000;Labouvie & Bates, 2002;Montgomery et al, 1993) and problematic drinking (Kuntsche et al, 2005(Kuntsche et al, , 2008Lewis et al, 2008;Martens et al, 2008).…”
Section: P Ersonalized Normative Feedback (Pnf)mentioning
confidence: 99%